Women Criminality and Education for Sustainable Development: A Study of Abraka Kingdom - Lilian O. Itoje-Akpokiniovo; Omoriwhovo Enoch. O; Great Iruoghene Edo (Journal of Education for Sustainable Development Studies, 2025)
This research investigates whether education influences women to engage in criminal activities in Abraka Kingdom for the purpose of sustainable development. It investigates whether socio-economic as well as educational factors increase women’s participation in criminal behaviour and how education can reduce crime rates and promote long-term development. This is done through interviews, surveys, analysis of secondary data. This work showed that poverty, lack of employment and limited educational access affect female involvement in criminal activities. Women with limited education are more likely to steal, deceive and sell sex to survive because of financial problems and limited options. It says education prevents issues because it gives women the skills to get jobs, start businesses and fulfill social duties. The result indicates that education and job training for women is needed to empower them and reduce their risk of criminal activity. The study highlights constraints such as limited geographical scope, reliance on self-reported information and lack of long term analysis. The research found improving women’s education is essential to reduce female criminal behaviour and promote long-term sustainable development. It suggests policy measures, community education and government support for programs promoting women’s empowerment. Continuation studies should consider other locations, use long-term research methods and examine the effects of institutional policies on female criminals. To fill these gaps society could use education to prevent crime and promote sustainable development. The study contributes to conversations about gender, crime, and education by recommending measures to promote educational and socio-economic progress of women in Nigeria and other countries.